Predictable yet neglected: a review of Crimean Congo hemorrhagic fever outbreaks and response delays in Iraq (Journal of Ideas in Health, 2025)
Crimean-Congo Hemorrhagic Fever (CCHF) poses a significant and growing public health challenge in Iraq, with outbreaks occurring predictably each year during warmer months and primarily affecting rural, livestock-rearing regions. Despite the known seasonal and geographical patterns, public health responses remain largely reactive and delayed, contributing to higher incidence and case fatalities most notably in the large outbreaks of 2022 and 2023. Factors such as disrupted veterinary services during the COVID-19 pandemic, uncontrolled animal movements, and limited healthcare infrastructure have exacerbated the spread and severity of CCHF. This review highlights the persistent gaps in proactive surveillance, intersectoral collaboration, and preventive measures in Iraq, contrasting them with more effective strategies implemented in neighboring countries. To mitigate future outbreaks, a strengthened One Health approach is urgently needed, incorporating continuous tick and animal surveillance, targeted acaricide treatment, regulation of animal slaughter, and enhanced public education. Improved national coordination and resource allocation are critical to transitioning from a reactionary stance to a sustainable, preventative framework against CCHF in Iraq..
Keywords: Crimean-Congo Hemorrhagic Fever (CCHF); Predictable; Outbreak; COVID-19 impact; Iraq